USING STORY FACE STRATEGY IN TEACHING READING NARRATIVE TEXT AT JUNIOR HIGH SCHOOL - Maitri Lusiana; Yetti Zainil (Universitas Negeri Padang, 2018)
This paper discusses how to use Story Face Strategy in teaching reading narrative text at Junior High School. Based on the writers‟ experience in teaching English, many students find the difficulties in reading narrative text. Considering this problem, the teacher needs to apply a strategy in teaching and learning process to help the students understand the text. Story Face Strategy is a graphic organizer that aids reading comprehension of narrative text. Story face is constructed by making the eyes: two circles representing the setting and main characters, eyelashes: specific descriptors and secondary characters, nose: problem, and mouth: comprises a series of circles representing the main events that lead to the solution. It functions like a story map, allowing students to visualize the important component of narrative text, including setting, main characters, problems, events, and a resolution. By applying the Story Face Strategy in reading narrative text, the teacher can reach the goal of teaching narrative text to junior high school students. Key words: reading, narrative text, story face strategy